Systematic review of the effectiveness of community-based self-management interventions among primary care COPD patients. (December 2018) - Jolly, K.; Sidhu, M.; Bates, E.; Majothi, S.; Sitch, A.; Bayliss, S.; Kim, H.; Jordan, R.
Abstract COPD self-management reduces hospital admissions and improves health-related quality of life (HRQoL). However, whilst most patients are managed in primary care, the majority of self-management trials have recruited participants with more severe disease from secondary care. We report the findings of a systematic review of the effectiveness of community-based self-management interventions in primary care patients with COPD. We systematically searched eleven electronic databases and identified 12 eligible randomised controlled trials with seven included in meta-analyses for HRQoL, anxiety and depression. We report no difference in HRQoL at final follow-up (St George's Respiratory Questionnaire total score −0.29; 95%CI −2.09, 1.51;I 2 0%), nor any difference in anxiety or depression. In conclusion, supported self-management interventions delivered in the community to patients from primary care do not appear to be effective. Further research is recommended to identify effective self-management interventions suitable for primary care populations, particularly those with milder disease. Chronic Lung Disease: Towards effective self-management in primary care Further work is needed to ensure that self-management of chronic lung disease in primary care settings actively improves patients' quality of life. While self-management is beneficial to patients in secondary care with severe chronic obstructive pulmonary disease (COPD), few studies have examined self-management effectiveness in primary care patients with milder COPD. Kate Jolly at the University of Birmingham, UK, and co-workers identified only 12 studies out of over 12, 500 that specifically examined self-management in primary care. Of these, seven were suitable for metanalysis. The team found that community-based interventions to support self-management did not make a significant difference to patients' perceived quality of life, or in reducing anxiety and depression. They call for further research to identify specific support that will help patients with mild to moderate COPD cope and adapt to the progressive condition.